2013
DOI: 10.1038/nrn3516
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional control of pain and its disruption in chronic pain

Abstract: Chronic pain is one of the most prevalent health problems in our modern world, with millions of people debilitated by conditions such as back pain, headache and arthritis. To address this growing problem, many people are turning to mind–body therapies, including meditation, yoga and cognitive behavioural therapy. This article will review the neural mechanisms underlying the modulation of pain by cognitive and emotional states — important components of mind–body therapies. It will also examine the accumulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
1,253
2
34

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,558 publications
(1,413 citation statements)
references
References 179 publications
(164 reference statements)
45
1,253
2
34
Order By: Relevance
“…More recently, we also demonstrated that the mPFC is involved in the mediation of empathy for pain in rats, a phenomenon in which the mechanical pain sensitivity and spinal nociceptive responses of rats are dramatically increased after social interaction with a cagemate (but not a non-cagemate) in pain [15]. These results imply that the mPFC is one of the key brain structures involved in the cognitive and emotional modulation of pain [11,15,16]. As for the action of ethanol in the central nervous system, some in vitro brain slice studies have shown that ethanol facilitates the release of neurotransmitters such as c-aminobutyric acid (GABA), dopamine, serotonin, and opioids, whereas it inhibits glutamate activity, resulting in alterations in behavior [1].…”
Section: Introductionmentioning
confidence: 67%
“…More recently, we also demonstrated that the mPFC is involved in the mediation of empathy for pain in rats, a phenomenon in which the mechanical pain sensitivity and spinal nociceptive responses of rats are dramatically increased after social interaction with a cagemate (but not a non-cagemate) in pain [15]. These results imply that the mPFC is one of the key brain structures involved in the cognitive and emotional modulation of pain [11,15,16]. As for the action of ethanol in the central nervous system, some in vitro brain slice studies have shown that ethanol facilitates the release of neurotransmitters such as c-aminobutyric acid (GABA), dopamine, serotonin, and opioids, whereas it inhibits glutamate activity, resulting in alterations in behavior [1].…”
Section: Introductionmentioning
confidence: 67%
“…Psychological aspect is a major part in the management of low back pain in most western societies, which first require the use of depression screening questionnaires [9], but the screen for psychological aspect require the presence of sophisticated psychological management plan for the patients including the use of cognitive based therapy, mindfulness therapies [10]. In developing countries, these modalities are not always present, so addressing the yellow flags and managing them as possible will be more convenient than depression screening.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is considered part of the limbic system and encodes emotional (dysphoria or negative affect) and motivational aspects of pain [62], as well as behavioral monitoring and response selection relevant to disadvantageous choices in addiction [63]. This region receives direct dopaminergic input from the VTA [64], and as such may reflect upon the altered state of cognitive control and motivation common to mood disorders comorbid with migraine.…”
Section: Anterior Cingulate Cortex In Pain and Rewardmentioning
confidence: 99%